2019
DOI: 10.1016/j.ejvs.2019.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Choice of First Emergency Room Affects the Fate of Patients With Acute Mesenteric Ischaemia: The Importance of Referral Patterns and Triage

Abstract: WHAT THIS PAPER ADDS Although delay is a key modifiable factor in the treatment of acute mesenteric ischaemia (AMI), few studies have sought modifiable targets to reduce this parameter. This study found that the key factor is the type of emergency room (ER) the patient first encounters. If this ER was non-surgical, the time to surgical operation was approximately 15 h and mortality 75%, compared with 10 h and 50% mortality if the first ER was surgical. This study illustrates that patient pathway is a potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 26 publications
0
27
0
Order By: Relevance
“…The preimaging phase was assessed in one study by Lemma and colleagues (2019) 26 . They determined an interquartile range of 2.7–10.6 hours from emergency department (ED) presentation to computed tomography (CT) interpretation (median 5.5 hours) and 2.8–12.9 hours from ED to diagnosis (median 6.5 hours).…”
Section: Resultsmentioning
confidence: 99%
“…The preimaging phase was assessed in one study by Lemma and colleagues (2019) 26 . They determined an interquartile range of 2.7–10.6 hours from emergency department (ED) presentation to computed tomography (CT) interpretation (median 5.5 hours) and 2.8–12.9 hours from ED to diagnosis (median 6.5 hours).…”
Section: Resultsmentioning
confidence: 99%
“…In uncommon situations where irresectable malignancy may cause dramatic ALGIB due to major vascular involvement by the tumour, the use of endovascular stents, where anatomically feasible, may improve quality of life and provide successful palliation [297]. [303,305]. One reason for this may be the variability in management as observed between centres contributing to NELA [299].…”
Section: Question 216mentioning
confidence: 99%
“…It should be kept in mind that there could be a silent on-going cardiac infarction behind any acute embolic event. It has been shown that 20% to 60% of patients with AMI are admitted to non-surgical emergency room such as internal medicine, and this may cause a significant delay of the diagnosis ( 2 , 11 ). In addition, D-dimer may be elevated in embolic occlusion of the SMA ( 4 ).…”
Section: Clinical Presentation Of Embolic Amimentioning
confidence: 99%